Delineating the environmental justice implications of an experimental cheetah introduction project in India - Joshi, Yashendu C.; Klarmann, Stephanie E.; de Waal, Louise C. (Frontiers in Conservation Science, 2025)
Project Cheetah in Kuno National Park was initiated to establish a population of African cheetahs in India due to the Asiatic subspecies’ extinction in the country since the 1950s. The project has received criticism from international conservationists for lacking conservation and scientific merit. Conservationists, particularly from India and South Africa, have raised concerns regarding the ecological criteria guiding its decision-making and concerns regarding a lack of scientific evidence in addition to potential political motivations. The concerns raised by the international community suggest that the project may not solely focus on conserving the African cheetah, which is classified as “Vulnerable” by the International Union for Conservation of Nature (IUCN), but could be guided by other agendas outside of conservation. Several cheetahs have died in the project’s couple of years, raising ethical concerns regarding the cheetahs’ welfare and high mortality rates demonstrated thus far, in addition to the perceived unjust social impacts on local stakeholders. In this perspective piece, we use Project Cheetah as a case study to exemplify broader issues applicable to rewilding and restoration projects that necessitate attention by proponents and authorities responsible for issuing the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) import and export permits.